Prototype Visualisasi Karakter Unsur Kimia Dengan Teknologi Augemented Reality (AR) - Nashiruddin Alfath; Frans Santoso (Jurnal Teknologi Informasi dan Terapan, 2023)
Abstrac-This study aims to visualize the character of the chemical elements in the periodic table using Augmented Reality (AR) technology. Qualitative research methods with a design thinking approach. The design thinking stages consist of: empathy, determination, ideas, prototypes and trials. This AR technology was developed using Unity and Vuforia software. The results of the research are in the form of a prototype visualization of the characters of the chemical elements francium, hydrogen and calcium which can be viewed in three dimensions and projected into AR technology so that the user experience when viewing the prototype feels very real and interactive. This AR technology can be an alternative to understand the characteristics of the chemical elements on the periodic table. Keywords: Augmented Reality, prototype, character visualization, chemical elements.